PANDANGAN ULAMA KONTEMPORER DAN MAJELIS PERMUSYAWARATAN ULAMA KABUPATEN PIDIE TERHADAP ZAKAT INVESTASI PROPERTI - Mustajab, Muhammad; Zahara, Cut Naza (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to determine the criteria for property investment zakat in the view of Fiqh, the opinions of Contemporary Ulama on property investment zakat and the views of the MPU of Pidie Regency on property investment zakat. This type of research is field research using descriptive analysis methods. Data collection uses observation, interview, and documentation techniques. The results of the study indicate that the criteria for property investment zakat in the view of fiqh are houses if rented for rental or boarding houses. Hotels and properties that are rented Vehicles such as car rentals, buses, boats, ships, trucks and even airplanes. Factories and industries that produce goods such as rice mills and so on. The opinion of Contemporary Ulama on Property Investment Zakat is mandatory, the system for determining property investment zakat (al-mustaghallat) is to determine the end of the current zakat year (haul), the nisab of zakat on assets is worth 85 grams of 21 carat gold calculated based on the mandatory market price. The amount of property zakat is 2.5% for haul. The view of the MPU of Pidie Regency. Pidie regarding property investment zakat is categorized as income zakat, but property investment zakat is not required to be paid by the community, because generally the Pidie community adheres to the Shafi'i school of thought. According to the Shafi'i school of thought, there is no text of the Qur'an or hadith that stipulates paying property investment zakat.